Friction and wear behaviour of borided AISI 304 stainless steel with nano particle and micro particle size of boriding agents - Gunen, A.; Ulutan, M.; Gok, M.S.; Kurt, B.; Orhan, N. (Scibulcom Ltd., 2014)
In this study, AISI 304 stainless steel was subjected to solid boriding treatmentwith 10-50 nm particle size Nanoboron and commercially EKabor 3 powders.Processes were carried out at temperatures of 1223 and 1273 K for 2 and 4 hof treatment. Friction and wear behaviour of the samples borided with differentsizes of boriding agents has been examined. Wear experiments were performedby reciprocating a sliding wear test at dry conditions. After the wear tests, weartrack area, wear track volume and wear rate were calculated based on the surfaceof the worn materials. The samples borided with EKabor 3 and Nanoboronpowder showed 5 and 8 times higher wear resistance than non-borided AISI 304stainless steel, respectively. Borided steel samples were characterised by opticalmicroscopy, scanning electron microscopy (SEM), microhardness and X-ray diffractionanalyses (XRD). Metallographic studies showed that the boride layershave a flat and smooth morphology both in the AISI 304 steel and the boronpowder. The thickness and hardness of the boride layer measured between theranges of 23-33 ?m in thickness, 1020-1264 HV0.01 for EKabor 3 and 49-67 ?m,1880-2200 HV0.01 for boron nano-particles, depend on the boriding time and temperature.
Keywords: Boriding; Friction; Nanoboron; Reciprocating sliding; Wear